Pengaruh E-filling sebagai upaya meningkatkan kepatuhan pelaporan pajak di Kantor Pelayanan Pajak Pratama Maros - Sri Wahyuni Wiradika; Ilham Ilham; Sri Nirmala Sari (Income Journal: Accounting, Management and Economic Research, 2022)
This study aims to found out how the effect of E-filling as an effort to increase tax reporting compliance in the Maros Primary Tax Service Office. The type of data that used is primary data obtained through questionnaires distributed to individual taxpayers at the Maros Primary Tax Office. The population in this study are all taxpayers registered in the Maros Primary Tax Office. The data analysis technique that used is simple regression statistical analysis. The results showed that, Variable E-filling partially had a significant effect on the level of compliance of taxpayer reporting. This shows that in the application of E-filling can increase the level of taxpayer compliance in reporting tax